Analisis Fundamental Mikro dan Struktur Modal terhadap Nilai Perusahaan Tekstil BEI Melalui Profitabilitas (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasingly tight competition in the textile and garment industry has led to the optimal management of capital structure and microfinance to increase the value of the company. This study aims to analyze the influence of microfinance and capital structure on the value of the company with profitability as an intervening variable. The method used is a quantitative method with secondary data obtained from the financial reports of textile and garment companies registered in the Indonesian Financial Services Authority for the period 2020–2024. Data analysis was conducted using Structural Equivalence Modeling-Partial Least Square (SEM-PLS). The results of the study indicate that microfinance has a positive and significant effect on profitability and firm value. Meanwhile, capital structure has a positive but insignificant effect on profitability and a negative and insignificant effect on firm value. Profitability is proven to have a positive and significant effect on firm value, but is unable to mediate the influence of microfinance and capital structure on firm value. Thus, the findings of this study confirm that profitability fails to be an integrating variable.